2014
DOI: 10.3389/fpsyg.2014.01079
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of placebo responses: a systematic review of the literature

Abstract: Objective: Predicting who responds to placebo treatment-and under which circumstances-has been a question of interest and investigation for generations. However, the literature is disparate and inconclusive. This review aims to identify publications that provide high quality data on the topic of placebo response (PR) prediction. Methods:To identify studies concerned with PR prediction, independent searches were performed in an expert database (for all symptom modalities) and in PubMed (for pain only). Articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 58 publications
5
113
0
1
Order By: Relevance
“…Although some studies indicate a personality characteristic (for example, anxiety) to be associated with a higher placebo response in specific experimental and clinical settings, for example, in motion sickness and pain, 120 poor evidence has been collected that this association is true across all conditions tested. Certainly, a strong publication bias is present, as most investigators use a large battery of psychometric tests and usually report only those that were found to be linked to the placebo response and statistically nonsignificant results are often not published.…”
Section: Personalitymentioning
confidence: 89%
“…Although some studies indicate a personality characteristic (for example, anxiety) to be associated with a higher placebo response in specific experimental and clinical settings, for example, in motion sickness and pain, 120 poor evidence has been collected that this association is true across all conditions tested. Certainly, a strong publication bias is present, as most investigators use a large battery of psychometric tests and usually report only those that were found to be linked to the placebo response and statistically nonsignificant results are often not published.…”
Section: Personalitymentioning
confidence: 89%
“…due to previous experiences) and different types of pain (e.g. acute vs. chronic pain) (Horing et al., 2014; Peerdeman et al., 2016). Furthermore, participants received standardized and detailed instructions for the imagery exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, we published a review 85 screening the respective literature on personality and placebo response and found 21 studies, most with pain as the dependent variable. Most predictors of the placebo response were psychological constructs related to actions, expected outcomes, and the emotional valence attached to these events (eg, goal seeking, self-efficacy or self-esteem, locus of control, and optimism).…”
Section: The Search For Predictors Of Experimental Placebo Responsesmentioning
confidence: 99%